2014
DOI: 10.1007/s40750-014-0014-0
|View full text |Cite
|
Sign up to set email alerts
|

Close Versus Decisive Victory Moderates the Effect of Testosterone Change on Competitive Decisions and Task Enjoyment

Abstract: Prior research found that testosterone change after defeat predicted the decision to compete against the same opponent, but testosterone change after victory was unrelated to competitive behavior. The present research tested whether testosterone responses have differential effects on competitive decision-making depending on whether an individual either barely or decisively won a competition. Seventy-one undergraduate males provided an afternoon saliva sample and then participated in a laboratory cognitive cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 64 publications
3
38
0
Order By: Relevance
“…This approach is based on the dual-hormone and triple imbalance hypotheses (Mehta & Josephs, 2010;Terburg et al, 2009). In this regard, T boosts reward sensitivity (Mehta, Snyder, Knight, & Lassetter, 2015), approach behavior, and appetitive motivation (Op De MacKs et al, 2011), whereas C is associated with behavioral inhibition (Dickerson & Kemeny, 2004;Roelofs et al, 2009). Thus, it has been suggested that higher basal T levels may induce reward-seeking and more risk-taking behaviors when C is not inhibiting these behaviors (Mehta, Welker, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is based on the dual-hormone and triple imbalance hypotheses (Mehta & Josephs, 2010;Terburg et al, 2009). In this regard, T boosts reward sensitivity (Mehta, Snyder, Knight, & Lassetter, 2015), approach behavior, and appetitive motivation (Op De MacKs et al, 2011), whereas C is associated with behavioral inhibition (Dickerson & Kemeny, 2004;Roelofs et al, 2009). Thus, it has been suggested that higher basal T levels may induce reward-seeking and more risk-taking behaviors when C is not inhibiting these behaviors (Mehta, Welker, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research in humans also demonstrates connections between testosterone and status-seeking behavior (for reviews, see Mazur and Booth, 1998;Archer, 2006;Eisenegger et al, 2011;Hamilton et al, 2015). Both endogenous testosterone and exogenously elevated testosterone are positively related to markers of dominance motivation (van Honk et al, 2001;Schultheiss et al, 2005;Josephs et al, 2006;Hermans et al, 2008;Bos et al, 2012;Terburg et al, 2012;Terburg and van Honk, 2013;Goetz et al, 2014;Enter et al, 2014;Radke et al, 2015;Mehta et al, 2008;Zilioli and Watson, 2013;van der Meij et al, 2016), aggressive behavior (CarrĂ© et al, 2009;CarrĂ© and Olmstead, 2015), competitive behavior CarrĂ© and McCormick, 2008;Mehta et al, 2008Mehta et al, , 2009Slatcher et al, 2011;Mehta et al, 2015bMehta et al, , 2015cReimers and Diekhof, 2015;Hahn et al, 2016;Eisenegger et al, 2016), and reduced prosocial behaviors including trust, perspective-taking, cooperation, and empathy (Hermans et al, 2006;Mehta et al, 2009;Bos et al, 2010;van Honk et al, 2011;Boksem et al, 2013;Wright et al, 2012;Ronay and Carney, 2013;Edelstein et al, 2014).…”
mentioning
confidence: 99%
“…This theorizing is informed by evidence that testosterone enhances activity in dopaminergic neural reward regions such as the ventral striatum (Packard et al, 1997;Hermans et al, 2010;Op de Macks et al, 2011). Testosterone is also positively related to psychological factors linked to reward, such as task enjoyment and positive affect (Amanatkar et al, 2014;Mehta et al, 2015bMehta et al, , 2015c. Null effects of testosterone on psychological factors implicated in reward have also been reported (e.g., non-significant effects of testosterone on mood: Aarts and van Honk, 2009;Bos et al, 2010;Terburg et al, 2012), but these studies did not investigate interactions with cortisol.…”
mentioning
confidence: 99%
“…Indeed, considerable research has found an association between testosterone and competitive, status-seeking behavior (reviewed in Casto & Mehta, this volume; Geniole & CarrĂ©, this volume). Competition-induced testosterone changes are influenced by competitive outcome (i.e., win vs. loss; e.g., Gladue, Boechler, & McCaul, 1989;Mazur, Booth, & Dabbs, 1992;Mehta, Snyder, Knight, & Lassetter, 2015;Pound, Penton-Voak, & Surridge, 2009), and these testosterone fluctuations may in turn influence future competitive behavior by promoting such behavior when it may enhance status (discussed in Mehta et al, 2015). A methodological limitation of this (and other) work is reliance on correlations instead of experimental manipulations, which, particularly given that the relationships between testosterone and aggressive and competitive behavior are Subscriber: OUP-Reference Gratis Access; date: 14 May 2019 bidirectional (i.e., the behavior follows the increase in the hormone and vice versa; e.g., CarrĂ©, Campbell, Lozoya, Goetz, & Welker, 2013;Geniole, Bird, Ruddick, & CarrĂ©, 2017), does not inform our knowledge of causal relationships.…”
Section: Social and Affective Behaviormentioning
confidence: 99%